1977
DOI: 10.1055/s-0028-1097516
|View full text |Cite
|
Sign up to set email alerts
|

ANTIINFLAMMATORY PRINCIPLES OFCAESALPINIA SAPPANWOOD AND OFHAEMATOXYLON CAMPECHIANUMWOOD1

Abstract: C a e s a l p i n i a s a p p a n wood has been evaluated for its antiinflammatory effects based on its traditional usage in Oriental medicine to reveal that it is active in the fertile egg assay. Then, its extract has been fractionated monitored by the physiological activity, resulting in the isolation of brazilin as the actiue principle. Brazilin, together with hematoxylin a constituent o f H a e m a t o x y 1 o n c a mp e c h i a n u m wood, have been subjected to various antiinflammatory assays. Both the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0
3

Year Published

1985
1985
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 2 publications
2
43
0
3
Order By: Relevance
“…Previous studies of species of the genus Caesalpinia, Fabaceae, report remarkable biological activities, such as antimicrobial (Saeed & Sabir, 2001), antidiabetic (Sharma et al, 1997) (C. bonducella), antimalarial (Deharo et al, 2001;Kuria et al, 2001) (C. volkensii, C. pluviosa), and anti-infl ammatory (Hikino et al, 1977;Carvalho et al, 1996) (C. sappan, C. ferrea) activities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of species of the genus Caesalpinia, Fabaceae, report remarkable biological activities, such as antimicrobial (Saeed & Sabir, 2001), antidiabetic (Sharma et al, 1997) (C. bonducella), antimalarial (Deharo et al, 2001;Kuria et al, 2001) (C. volkensii, C. pluviosa), and anti-infl ammatory (Hikino et al, 1977;Carvalho et al, 1996) (C. sappan, C. ferrea) activities.…”
Section: Introductionmentioning
confidence: 99%
“…anticomplementary, 5) modulation of immune function, 6) hepatoprotective, 7) antiinflammatory, 8) cytotoxic, 9) hypoglycemic 10) and several other biological activities have been reported. 1) Several triterpenoids, 11) flavonoids, 12,13) phenolics, 12,14,15) steroids 11) have been isolated from the heartwood.…”
mentioning
confidence: 99%
“…Brazilin is the major constituent of C. sappan. It was previously reported that brazilin (7,11b-dihydrobenz[b]indeno [1,2-d]pyran-3,6a,9,10(6H)-tetrol), the major component of C. sappan [16], showed antiplatelet activity through the inhibitory effects on PLA 2 activity and the increase in intracellular free Ca 2+ concentration ([Ca 2+ ] i ; [17]). These results suggest that brazilin could be a new lead compound in the development of antiplatelet agents.…”
Section: Introductionmentioning
confidence: 99%